Did smoking behavior change in adolescents and young adults with and without diabetes during the COVID-19 pandemic? A cohort study from the DPV registry - Katharina Warncke; Sabine E. Hofer; Simone von Sengbusch; Uwe Ermer; Mareike Niemeyer; Andreas Lemmer; Dörte Hilgard; Alena Welters; Reinhard W. Holl; Alexander J. Eckert (BMC Pediatrics)
Abstract Background Smoking is a risk factor for cardiovascular complications and can promote a severe course of COVID-19 infection. The aim of this study was to compare smoking habits of young people with diabetes with the general population. Methods We analyzed smoking behavior in the Diabetes Prospective Follow-up Registry (DPV) cohort (type 1 (T1D) and type 2 diabetes (T2D) from Germany and T1D from Austria aged 14–24 years) and compared it to data from the German survey on smoking behavior (DEBRA study) of the general population. Data were aggregated per year and patient for 2016–2023. Logistic regression models adjusted for gender and migration background were calculated stratified by age groups (14–17; 18–24 years), taking repeated measurements into account. Smoking behavior between T1D and T2D or between Germany and Austria was compared with similar regression models. Results Thirty-four thousand two hundred seventy-five patients from the DPV cohort were included in data analysis. The overall proportion of people who smoked was lower in DPV than in the general population (13.4% vs. 24.0%), with the exception of young adults with T2D at the beginning of the pandemic (36.7% vs. 33.4%). For T1D, there was a significant upward trend in the number of patients who smoked in the group of 14–17 years (2.86%, CI 1.21–4.55 per year, p < 0.001) and also in the group of 18–24 years (4.94 per year, CI 1.37–8.63; p < 0.01) between 2016 and 2023. The proportion of smokers and the number of smoked cigarettes was higher in Austria than in Germany (10.7% vs. 8.0%; OR with 95%-CI 1.38 [1.22–1.56], p < 0.001; and 7.5 [6.8–8.1] vs. 5.9 [5.7–6.0] cigarettes/day, p < 0.001) and in T2D than T1D (11.0% vs. 7.9%; OR 1.44 [1.23–1.68], p < 0.001 and 8.0 [7.2–8.8] vs. 5.9 [5.7–6.1] cigarettes/day, p < 0.001). Conclusion The reported proportion of smokers among young people with diabetes was lower than in the general population. Only young adults with T2D temporarily smoked more than the general population at the beginning of the pandemic. This could be explained by stress, but also by a changed daily structure during the lockdown.